Conceptualising Risk and Need: The Rise of Actuarialism and the Death of Welfare? Practitioner Assessment and Intervention in the Youth Offending Service. (April 2013) - Briggs, Damon B.
This article is concerned with the assessment and intervention strategies and processes employed by practitioners working within the Youth Offending Service (YOS) in England and Wales. It draws on interview data with YOS practitioners to investigate assessment and intervention rationales and conceptions of both 'risk' and 'need' against a backdrop of shifting ideologies and modes of governance in youth justice. The article revisits macro theories of risk and the 'risk society', explores theories of modern penality and how conceptions of risk have permeated contemporary youth justice policy and practice through actuarial frameworks of assessment. It is argued that competing rationales in YOT practitioners' assessments and interventions reveal an active struggle where, despite a managerial/actuarial milieu, some practitioners continue to hold the welfare needs of young people as paramount. The article then reflects on current youth justice policy under the Conservative–Liberal Democrat Coalition Government and the effect that their proposed changes may have on practice.